DIP2C polymorphisms are implicated in susceptibility and clinical phenotypes of autism spectrum disorder. (October 2022) - Li, Yan; Sun, Chuanyong; Guo, Yanbo; Qiu, Shuang; Li, Yong; Liu, Yunkai; Zhong, Weijing; Wang, Hedi; Cheng, Yi; Liu, Yawen
Highlights: rs3740304, rs2288681, and rs7088729 are positively associated with ASD under inheritance models;. Haplotypes with any two marker SNPs (rs3740304 [G], rs2288681 [C], rs7088729 [T], rs4242757 [C], rs10795060 [G], and rs10904083 [A]) are also significantly associated with ASD;. rs10795060 and rs10904083 are associated with "visual reaction" phenotypes of ASD. Abstract: Background: Disco-interacting protein 2 C ( DIP2C ) has recently been reported as a new susceptibility gene for autism spectrum disorder (ASD) in a genome-wide association study. Methods: We evaluated associations between single nucleotide polymorphisms (SNPs) of DIP2C and ASD susceptibility in a case-control study (715 ASD cases and 728 controls) from Chinese Han. Results: We identified a significant association between SNPs (rs3740304, rs2288681, rs7088729, rs4242757, rs10795060, and rs10904083) and ASD susceptibility. Of note, rs3740304, rs2288681, and rs7088729 are positively associated with ASD under inheritance models; moreover, haplotypes with any two marker SNPs (rs3740304 [G], rs2288681 [C], rs7088729 [T], rs4242757 [C], rs10795060 [G], and rs10904083 [A]) are also significantly associated with ASD. Additionally, rs10795060 and rs10904083 are associated with "visual reaction" phenotypes of ASD. Conclusions: DIP2C polymorphisms sort out the susceptibility and clinical phenotypes of autism spectrum disorder.